ANALISIS KEDUDUKAN WALI HAKIM SEBAGAI WALI NIKAH PENGGANTI DALAM HUKUM ISLAM PERSPEKTIF MAZHAB SYAFI'I - Aswat, Hazarul; Hidayat, Taufik (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Marriage in Islamic law requires the fulfillment of certain conditions and pillars, including the presence of a guardian (wali) for the marriage. The guardian plays a crucial role in ensuring that the marriage is conducted in accordance with religious guidelines. This study aims to analyze the transition of the role of nasab guardians to that of judicial guardians in marriage practices according to Islamic law, as well as to understand the implications of this transition in the context of contemporary society. The research employs a library research method with a normative approach, exploring literature and references from various sources, including fiqh texts and scholars' opinions. The findings reveal that marriage guardians consist of wali mujbir, who is a nasab guardian, and wali hakim, who acts as a substitute when the nasab guardian is unable to fulfill their duty. The criteria for appointing a wali hakim based on scholarly ijtihad provide flexibility in marriage practices. This research contributes to understanding the dynamics of guardianship in marriage and clarifies the provisions for wali hakim according to the Shafi'i school of thought. The results are expected to serve as a reference and guideline for the community in conducting marriages in accordance with Islamic principles.